Exploring and developing effective evaluative approaches for evidencing the contribution of CCAFS climate data and tools towards development outcomes - Rassmann, Kornelia; Schuetz, Tonya; Thornton, Philip K.; Cramer, Laura K. (2017)
Do CCAFS’ climate data and tools contribute to development outcomes? The production of International PublicGoods (IPGs) – such as high quality, easy to use climate data and tools – is part of CGIAR CCAFS’ delivery promise. With CCAFS’ transition to a results-based management approach there is an increased focus on achieving development outcomes. Hence, resources have to be balanced between i) IPG development, maintenance & support, ii) programs aiming to deliver development outcomes employing these IPGs, and iii) monitoring and evaluation efforts to assess such programs.